2020
DOI: 10.7196/samj.2020.v110i10.14814
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of paediatric preoperative fasting times at Red Cross War Memorial Children’s Hospital, Cape Town, South Africa

Abstract: Background. Fasting for liquids and solids is recommended prior to procedures requiring anaesthesia, to reduce the risk of pulmonary aspiration. Children often experience excessive fasting, which is associated with negative physiological and behavioural consequences, and patient discomfort. The duration of preoperative fasting in children in South Africa (SA) is unknown. Objectives. To determine compliance with fasting guidelines and fasting times of children prior to elective procedures performed under anaest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Fasting time from drinking is di cult to control accurately, and most of the time there is a delay, mainly due to parental concerns, and surgical anesthesia departmental articulation (9,13). In A J Kouvarellis' study, it was similarly found that there was a large discrepancy between clinical and guidelines and that systematic quality improvement was needed to make it possible to reduce the discrepancy (14).…”
Section: Discussionmentioning
confidence: 99%
“…Fasting time from drinking is di cult to control accurately, and most of the time there is a delay, mainly due to parental concerns, and surgical anesthesia departmental articulation (9,13). In A J Kouvarellis' study, it was similarly found that there was a large discrepancy between clinical and guidelines and that systematic quality improvement was needed to make it possible to reduce the discrepancy (14).…”
Section: Discussionmentioning
confidence: 99%
“…19 O jejum prolongado pré-operatório, em que os pacientes não podem ingerir líquidos ou sólidos por via oral, 13 para garantir o esvaziamento gástrico e evitar a broncoaspiração durante o procedimento cirúrgico 11 não apresenta uma boa adesão. 5 A redução do tempo de jejum de líquidos irá resultar em benefícios consideráveis, mitigando o emocional negativo, comportamento, bioquímico e hemodinâmico e melhoria dos escores de dor. 8 Os tempos de jejum prolongado causa um desequilíbrio da homeostase metabólica, diminuição da pressão arterial, cetoacidose e tem um efeito negativo no estado de hidratação, causando irritabilidade na criança, reduzindo a satisfação dos pais, 13 fome e sede intensos resultaram numa experiência pré-operatória ruim para crianças.…”
Section: Estratégias Relacionadas Ao Preparo Pré-operatóriounclassified
“…Toward Solving the Prolonged Fast: Better Communication Parental noncompliance with the 2-hour fast after clears has been attributed to a panoply of reasons, [71][72][73][74][75] leading to our senses of frustration and futility in resolving this issue. Two quality improvement studies streamlined hard-copy instructions to parents, reminded parents to follow the 2-hour fast after clears in a phone call on the evening before surgery, and included oral administration of limited clear liquids in hospital to select patients.…”
Section: Vascular Accessmentioning
confidence: 99%